Validation of the Italian Tinnitus Questionnaire Short Form (TQ 12-I) as a Brief Test for the Assessment of Tinnitus-Related Distress: Results of a Cross-Sectional Multicenter-Study - Moschen, Roland; Fioretti, Alessandra; Eibenstein, Alberto; Natalini, Eleonora; Cuda, Domenico; Chiarella, Giuseppe; Rumpold, Gerhard; Riedl, David (Frontiers in Psychology, 2018)
Objectives: The use of reliable and valid psychometric tools to assess subjectively experienced distress due to tinnitus is broadly recommended. The purpose of the study was the validation of the Italian version of Tinnitus Questionnaire 12 item short form (TQ 12-I) as a brief test for the assessment of patient reported tinnitus-related distress. Design: Cross-sectional multicenter questionnaire study. Setting: Tinnitus Center, European Hospital (Rome), the Department of Otorhinolaryngology, “Guglielmo da Saliceto” Hospital (Piacenza), and the Department of Audiology and Phoniatry, “Mater Domini” University Hospital (Catanzaro). Participants: One hundred and forty-three outpatients with tinnitus treated at one of the participating medical centers. Main Outcome Measures: Tinnitus Questionnaire Short Form (TQ 12-I), compared to the Tinnitus Handicap Inventory (THI), Brief Symptom Inventory (BSI), and Short Form (SF-36) Health Survey. Results: Our factor analysis revealed a two-factor solution (health anxiety, cognitive distress), accounting for 53.5% of the variance. Good internal consistency for the total score (α = 0.86) and both factors (α = 0.79–0.87) was found. Moderate correlations with the THI (r = 0.65, p < 0.001) indicated good convergent validity. Tinnitus distress was further correlated to increased psychological distress (r = 0.31, p < 0.001) and reduced emotional well-being (r = -0.34, p < 0.001). Conclusion: The study clearly showed that the TQ 12-I is a reliable and valid instrument to assess tinnitus-related distress which can be used in clinical practice as well as for research.